SOME ASPECTS OF MEDIEVAL EASTERN RATIONALISM: A CONCEPTUAL ANALYSIS - B.M.Negmatov (Scholar Express Journals, 2023)
The article analyzes the unique views of Farabi and Ibn Sina, the great thinkers of the East, about the mind, its status and possibilities as the highest criterion of the cognitive process.
Keywords: cognition; cognitive process; live observation